Role of Neurotransmitters (Biomediators) in Plant Responses to Stress - Zahra Dehghanian; Mohammad Ahmadabadi; Behnam Asgari Lajayer; Nazila Bagheri; Masoud Chamani; Vahideh Gougerdchi; Mohsen Hamedpour-Darabi; Weixi Shu; G. W. Price; Bernard Dell (Plants)
Plants possess a complex signaling system that enables them to sense and adapt to various environmental stressors, including abiotic factors like extreme temperatures, drought, salinity, and toxic heavy metals. While the roles of hormones and signaling molecules in plant stress responses are well established, the involvement of neurotransmitters—traditionally linked to animal nervous systems—in plant stress physiology is a relatively underexplored area. Recent findings indicate that neurotransmitters such as gamma-aminobutyric acid, glutamate, serotonin, and dopamine play crucial roles in several physiological processes within plants. They regulate ion channels, adjust stomatal movements, modulate the production of reactive oxygen species, and influence gene expression. Evidence suggests that these neurotransmitters enhance antioxidant defense mechanisms and regulate stress-responsive pathways vital for plant stress tolerance. Additionally, under stressful conditions, neurotransmitters have been shown to impact plant growth, development, and reproductive activities. This review aims to illuminate the emerging understanding of neurotransmitters as key biomediators in plant responses to abiotic stress.